2014
DOI: 10.1517/14712598.2015.963052
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies for the treatment of non-haematological tumours: update of an expanding scenario

Abstract: (2015) Monoclonal antibodies for the treatment of non-haematological tumours: update of an expanding scenario, Expert Opinion on Biological Therapy, 15:1, 45-59,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Cancer immunotherapy is emerging as a very promising therapeutic strategy for several solid tumors, including non-small cell lung cancer (NSCLC). Differently from other treatment approaches directed against the tumor, such as chemotherapy or targeted therapy [ 1 - 6 ], targeting the immune system offers the potential for durable activity and long-term survival outcomes, regardless of tumor's histological subtype or mutation status, with a unique, tolerable, toxicity profile. Among the different immunotherapeutic strategies under clinical investigation in NSCLC, the blockade of inhibitory immune-checkpoints with monoclonal antibodies (MoAbs), is currently considered the most promising approach, promoting the immune-response against cancer cells [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer immunotherapy is emerging as a very promising therapeutic strategy for several solid tumors, including non-small cell lung cancer (NSCLC). Differently from other treatment approaches directed against the tumor, such as chemotherapy or targeted therapy [ 1 - 6 ], targeting the immune system offers the potential for durable activity and long-term survival outcomes, regardless of tumor's histological subtype or mutation status, with a unique, tolerable, toxicity profile. Among the different immunotherapeutic strategies under clinical investigation in NSCLC, the blockade of inhibitory immune-checkpoints with monoclonal antibodies (MoAbs), is currently considered the most promising approach, promoting the immune-response against cancer cells [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resection of the CLM, sometimes in combination with other local treatment modalities, such as radiofrequency ablation (RFA), has become the standard of care, and offers the only potential for cure (Chiappa et al, 2009;Ksienski et al, 2010). The development of new surgical approaches, together with an increasing use of the perioperative systemic therapy, have led to an increase of the percentage of patients potentially eligible for curative liver resection (Rolfo et al, , 2013Bronte et al, 2015Bronte et al, , 2013. In most series, up to 25% of patients presenting with stage IV CRC undergo hepatic resection (Kopetz et al, 2009), with reported 5-year survival rates up to 50% (Taylor et al, 2010;Choti et al, 2002;Chua et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these known signaling pathways, targeted systemic treatments have been specifically designed and approved: the humanized anti-VEGF monoclonal antibody bevacizumab [13, 14] in combination with IFN-α, four multitargeted tyrosine kinase inhibitors (TKIs): sorafenib, sunitinib, pazopanib and axitinib; and two kinase inhibitors of mTOR, temsirolimus and everolimus (Figure 1). …”
Section: Introductionmentioning
confidence: 99%